2017
DOI: 10.1002/jsfa.8685
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blueberry powder produced via foam‐mat freeze‐drying versus spray‐drying: evaluation of foam and powder properties

Abstract: BACKGROUND Blueberry juice powder was developed via foam‐mat freeze‐drying (FMFD) and spray‐drying (SD) via addition of maltodextrin (MD) and whey protein isolate (WPI) at weight ratios of MD/WPI = 0.4 to 3.2 (with a fixed solids content of 5 wt% for FMFD and 10 wt% for SD). Feed rates of 180 and 360 mL h−1 were tested in SD. The objective was to evaluate the effect of the drying methods and carrier agents on the physical properties of the corresponding blueberry powders and reconstituted products. RESULTS Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 41 publications
(64 reference statements)
4
53
0
2
Order By: Relevance
“…However, from this experiment, the F-FDPP sample tended more to be agglomerated when exposed to moisture from the environment during handling of the sample due to its porous structure, which allows moisture to be rapidly adsorbed into the structure (Darniadi et al, 2018). Raharitsifa and Ratti (2010b) found that F-FD samples were more hygroscopic than n-FD samples.…”
Section: Characteristics Of Pandan Powdermentioning
confidence: 77%
See 3 more Smart Citations
“…However, from this experiment, the F-FDPP sample tended more to be agglomerated when exposed to moisture from the environment during handling of the sample due to its porous structure, which allows moisture to be rapidly adsorbed into the structure (Darniadi et al, 2018). Raharitsifa and Ratti (2010b) found that F-FD samples were more hygroscopic than n-FD samples.…”
Section: Characteristics Of Pandan Powdermentioning
confidence: 77%
“…A high value of foam overrun means a large amount of air bubbles trapped inside the foam structure. In contrast, when the volume fraction of air decreases, the density of foam increases (Darniadi et al, 2018).…”
Section: Foaming Properties Of Pandan Leaf Extract As Affected By Dmentioning
confidence: 94%
See 2 more Smart Citations
“…Foam-mat freeze-drying and spray-drying (SD) were conducted according to the method of Darniadi et al, 21 The total solids fraction for all prepared foams for freeze-drying was fixed at 50 g/kg, while spray-drying was at 100 g/kg. Matrices of MD + WPI were prepared with ratios of MD/WPI = 0.4, 1.0, 1.6, 2.3 and 3.2.…”
Section: Foam-mat Freeze-drying (Fmfd) and Spray-drying (Sd) Of Bluebmentioning
confidence: 99%